The determinants of financial inclusion based on the ownership and frequency of use of financial accounts in the Philippines - Bulan, Karla Anne R.; Sanchez, Klandia Louise L.; Daway-Ducanes, Sarah Lynne S. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
This study explores the determinants of financial inclusion in the Philippines in terms of account ownership, frequency of use of account, and transacting with formal financial institutions. The factors include age, education, geographical areas, urbanization, gender, and income. Using data from the 2015 National Baseline Financial Inclusion Survey and the 2017 Financial Inclusion Survey, the results from probit regression analyses show that individuals who are older, more educated, female, richer, and living in NCR are more likely to own an account. Meanwhile, individuals who are female, older, more educated, living in NCR, and urban dwellers tend to transact more with formal financial institutions. Frequency of use of account does not have any significant factor from our explanatory variables. The study also finds that there is a variation in the magnitude and significance of the determinants in the different geographical areas (NCR, balanced Luzon, Visayas, and Mindanao). These results may help aid policy-makers in solving the problem of financial exclusion.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references.
Keywords: Finance -- Social aspects; Financial services industry -- Social aspects; Financial services industry -- Government policy; Financial exclusion; Equality